Clinically relevant aspects of professional follow-up care for implant patients - Sahrmann, Philipp; Giannopoulou, Catherine (Frontiers in Dental Medicine, 2025)
The detailed 2023 guidelines for the prevention and treatment of peri-implantitis describe evidence-based measures for the professional care and prevention in patients with dental implants. However, there remains a lack of reliable data from randomized clinical trials on many critical points, particularly regarding specific diagnostic steps and treatment decisions, to provide definitive guidance and protocols for implementation during recall sessions in daily practice. This narrative review seeks to address this gap by highlighting the critical aspects of follow-up care that should be monitored during periodontal maintenance to ensure the health of peri-implant tissues and enable timely intervention when peri-implant health is compromised.